Evaluation of the Implementation of the Occupational Health and Safety Program at the Tidore Islands City Regional General Hospital Based on SNARS Edition I - Mardia Habel; Gunawan Hi Ibra; Sitti Hartinah (Universitas Wiralodra, 2025)
Evaluation of the implementation of occupational health and safety programs in hospitals is an activity carried out to assess the quality of the program's effectiveness. Accreditation is an acknowledgment of the quality of hospital services. The accreditation standard used since January 1, 2018 is the SNARS Edition which consists of 16 chapters, one of which is health facility management (MFK) which contains risk management. This study is a study with a qualitative descriptive approach to evaluate the implementation of occupational health and safety programs in the Tidore Islands City Regional General Hospital using data analysis techniques in the form of data collection, data reduction and data presentation. Informants in this study amounted to 3 people consisting of key informants, regular and supporting. The results of this study indicate that the hospital has established policies related to K3, and has human resources who have decrees and certificates, has implemented safety and security programs, B3 management, disaster management, fire protection systems, medical equipment management and supporting systems. In the implementation of the program there are obstacles, namely: lack of human resources who are experts in the field of K3 and support related to funding. The conclusion of the implementation of the K3 program at the Tidore Islands City Hospital is that there are several shortcomings, including the hospital lacking human resources who are experts in the field of K3, the hospital does not yet have complete equipment related to active fire protection systems and early fire detection systems.